Schooling Jim Crow : the fight for Atlanta's Booker T. Washington High School and the roots of Black protest politics - Driskell, Jay Winston, 1973- (Carter G. Woodson Institute series., 2014)
"This book describes how the early NAACP successfully organized a voting bloc in 1920s Atlanta powerful enough to force the city to build its first publicly funded Black high school"--Provided by publisher